Mirative focalization: A case study of Mandarin lian-DP dou construction - Xing, Yue (LingBaW. Linguistics Beyond and Within, 2023)
The paper investigates Mandarin lian-DP dou construction (aka. ‘even’-construction) in terms of the following controversial aspects – i.e., the contributions of the syntactically indispensable elements lian ‘even’ and dou ‘all’, and the syntactic distribution of the construction in connection with associated information structure. It is extensively accepted in the literature that a lian-DP – i.e., the chunk formed by lian and the following nominal phrase, can represent two functional positions – in the clause-external Left Periphery (henceforth LP), and in the low IP area, because it occurs either preceding or following the alleged subject. In the present paper, however, I argue that a lian-DP, regardless of its linear position, undergoes successive-cyclic movement and, specifically, it first makes a stopover in SpecdouP for quantificational reasons before it takes a further step of mirative focus fronting targeting the LP. Support is threefold – pragmatically, lian-DP dou construction denotes contextually similar implicatures as Sicilian mirative expressions do; semantically, the quantifier dou, serving as a maximality operator, imposes exhaustivity over the alternatives available on a scale and therefore forces the lian-DP to move to SpecdouP; and syntactically, the observable weak crossover effects (WCO) manifest that lian-DP movement is inherently focus fronting.